Sonification: Review of Auditory Display Solutions in Electronic Travel Aids for the Blind - BUJACZ, Michał; STRUMIŁŁO, Paweł (Archives of Acoustics, 2016)
Sonification is defined as presentation of information by means of non-speech audio. In assistive technologies for the blind, sonification is most often used in electronic travel aids (ETAs) – devices which aid in independent mobility through obstacle detection or help in orientation and navigation. The presented review contains an authored classification of various sonification schemes implemented in the most widely known ETAs. The review covers both those commercially available and those in various stages of research, according to the input used, level of signal processing algorithm used and sonification methods. Additionally, a sonification approach developed in the Naviton project is presented. The prototype utilizes stereovision scene reconstruction, obstacle and surface segmentation and spatial HRTF filtered audio with discrete musical sounds and was successfully tested in a pilot study with blind volunteers in a controlled environment, allowing to localize and navigate around obstacles.